PELAKSANAAN ALIH FUNGSI LAHAN PERTANIAN MENJADI LAHAN NON PERTANIAN BERDASARKAN UNDANG-UNDANG NOMOR 26 TAHUN 2007 TENTANG TATA RUANG (Studi Kasus Di Desa Mojosongo Kabupaten Boyolali) - PUTRO, TULUS WASONO (Dinamika Hukum, 2018)
The purpose of this study is to: 1) Review and analyze the implementation of land use over the function from farmland into non agricultural land in the village of Mojosongo Boyolali district is in compliance with law No. 26-year 2007 concerning Spatial. 2) examines the obstacles in the implementation of land use over the function from farmland into non agricultural land in the village of Mojosongo Boyolali district is in compliance with law No. 26-year 2007 concerning Spatial as well as the efforts of overcoming barriers that occur in the implementation of land use over the function from farmland into non agricultural land. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of secondary. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) Execution permission over the function of farmland to non farm in the village of Mojosongo Boyolali Regency less in accordance with the regulations. It can be said so because in the village of Mojosongo land use changes to rice fields is done drying, this is certainly a violation of the regulations used in Boyolali district seeking control over the function of the land. Although the result of such land use change does not affect rice production results against Boyolali Regency, but the land use changes in the future will affect national rice needs, considering Boyolali Regency is one of the barns in Central Java province. Dikabulkannya of agricultural land use change to non farms, has also violated the provision in the Public Space of the City Plan (RUTRK) and Boyolali district, because the land is proposed for revamped its use be non farm land These do not comply with zoning-zoning that has been assigned in the plan of City Public Space (RUTRK) and Boyolali district. 2) barriers in the implementation of the land use change permissions against over use of farmland into home living in national land Agency Office/Agrarian and Spatial Boyolali Regency IE 1) Constraint Coordination policy, 2) Constraint Implementation of the policy and Planning Consistency Constraints) 3. The Government's effort in controlling Boyolali over the function of farmland to non-agricultural land is to certificate the soil for farmers who aims to provide certainty of rights and legal certainty over land ownership controlled the farming community and the society as a fast, precise, easy, inexpensive and secure, thus accomplishing the strengthening status of farmers ' land rights that used to be a plot of land of the dead be capital capital predicates active. Keywords: Agricultural Land, Farm, Non Farm